Carcinosarcoma of the ovary: a case report and literature review - Zheng, Jian; Tang, Cui; Liu, Ping; Hao, Hua (Frontiers in Oncology, 2023)
Objective: Carcinosarcoma of the ovary is a rare pathological type of ovarian cancer that is highly aggressive and occurs most frequently in the female reproductive tract at the site of the uterus. Herein, we explore the clinicopathological features, diagnosis, differential diagnosis, and treatment options for carcinosarcoma of the ovary. Methods: We analyzed the clinical data of a case of carcinosarcoma, observed its histological morphology and immunohistochemical characteristics, detected the homologous recombination repair deficiency gene mutation, and reviewed the relevant literature. Results: A 76-year-old menopausal woman visited our hospital because of abdominal distension, difficulty in urination, and constipation. Ultrasonography demonstrated abnormalities in the uterus and pelvic cavity, suggesting that the patient should undergo surgery. Immunohistochemical findings of carcinosarcoma of the right ovary were as follows: CK fraction (+), vimentin fraction (+), CK5/6 foci (+), p16 (+), p53 in approximately 70% (+), WT-1 foci (+), ER foci (+), PR part (+), Her-2 (1+), CK7 fraction (+), CK20 foci (+), CD99 fraction (+), CD10 fraction (+), CD56 foci (+), c-kit foci (+), SMA part (+), desmin foci (+), PD-L1 (-), SALL4 (-), OCT3/4 (-), p63 (-), p40 (-), D2-40 (-), inhibin (-), PLAP (-), CD30 (-), and Ki67 hotspot in approximately 80% (+). The patient underwent tumor cytoreduction and adjuvant chemotherapy. Currently, she is being followed up for 16 months and has a good general condition. Conclusions: The diagnosis of carcinosarcoma relies on histopathological examination and differentiation of carcinosarcoma from immature teratoma. The current therapeutic regimen for carcinosarcoma is still based on tumor cytoreduction and platinum-containing chemotherapy; research on targeted therapy is still in progress.